The sculpting of rectangular and jet-like morphologies in supernova remnants by anisotropic equatorially confined progenitor stellar winds. Issue 4 (9th January 2023) - Velázquez, P F; Meyer, D M-A; Chiotellis, A; Cruz-Álvarez, A E; Schneiter, E M; Toledo-Roy, J C; Reynoso, E M; Esquivel, A
ABSTRACT: Thermonuclear and core-collapse supernova remnants (SNRs) are the nebular leftovers of defunct stars. Their morphology and emission properties provide insights into the evolutionary history of the progenitor star. But while some SNRs are spherical, as expected from a point-like explosion expanding into a roughly uniform medium, many others exhibit complex non-spherical morphologies that are often not easily explained. In this work, we use 3D magnetohydrodynamic simulations to show that rectangular and jet-like morphologies can be explained by supernovae (SNe), either type Ia or type II, expanding within anisotropic, bipolar stellar wind bubbles driven by the progenitor star. The stellar wind has an anisotropic density distribution, which channels the SN ejecta differently depending on the anisotropy characteristics. We compute synthetic thermal (X-ray) and non-thermal (synchrotron) emission maps from our numerical simulations to compare with observations. We find rectangular morphologies are generated when the stellar wind has a high-mass loss rate and forms a dense, narrow disc at the equatorial region. Instead, a jet-like or ear-like morphology is obtained when the stellar wind develops a wide, dense disc. Stellar winds with low mass-loss rates do not strongly influence the SNR morphology. Finally, our synthetic synchrotron and X-ray maps for the high mass-loss rate case qualitatively agree with the observations of the SNRs G332.5-5.6 and G290.1-0.8.